1990
DOI: 10.1099/0022-1317-71-9-1905
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus satellite RNA (Y strain): analysis of sequences which affect yellow mosaic symptoms on tobacco

Abstract: Plants infected with cucumber mosaic virus (CMV) (KIN strain) produce a mild mosaic disease on tobacco whereas infections of CMV with satellite RNA (strain Y) cause a severe yellow mosaic. Analysis of recombinant and mutant forms of satellite RNA identified a site (nucleotides 185/186) in the Y satellite RNA that affects the ability to induce the yellow mosaic in combination with CMV but not with tomato aspermy virus. The location of this site with respect to other mutations in the satellite RNA indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 27 publications
(42 reference statements)
2
37
1
1
Order By: Relevance
“…If a virus-induced cascade targets mRNAs, there could be viral symptoms that are caused by silencing. There are several examples of viral or viroid RNAs that have properties predicted of silencing RNAs in that they induce symptoms but do not encode proteins (Devic et al 1989;Jaegle et al 1990;Wang et al 2004). However, there is no reason, in principle, that coding sequence viral RNAs could not also induce symptoms by silencing.…”
Section: Biological Implications Of Srna Cascadesmentioning
confidence: 99%
“…If a virus-induced cascade targets mRNAs, there could be viral symptoms that are caused by silencing. There are several examples of viral or viroid RNAs that have properties predicted of silencing RNAs in that they induce symptoms but do not encode proteins (Devic et al 1989;Jaegle et al 1990;Wang et al 2004). However, there is no reason, in principle, that coding sequence viral RNAs could not also induce symptoms by silencing.…”
Section: Biological Implications Of Srna Cascadesmentioning
confidence: 99%
“…Although most CMV satRNAs attenuate the symptoms induced by CMV in all host species tested, some satellite isolates intensify symptoms in certain hosts, for example inducing chlorosis in tomato and tobacco (Palukaitis, 1988) or necrosis in tomato (Takanami, 1981 ;Sleat et al, 1994). Sequences in the sat-RNA that control the symptom intensification have been mapped to specific nucleotide residues, and it has been shown that a few nucleotide sequence changes can alter the host response (Palukaitis, 1988 ;Masuta & Takanami, 1989 ;Jaegle et al, 1990 ;Sleat & Palukaitis, 1990 ;Sleat et al, 1994 ;Zhang et al, 1994). Furthermore, identical sat-RNAs can have different effects on symptoms when associated with different helper virus strains (Roossinck et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, symptoms in tomato aspermy virusinfected tobacco plants were greatly reduced by the presence ofthe satellite RNA of cucumber mosaic virus (CMV) but the amount of virus produced in the plants was not altered (23). Specific domains of nucleotides governing the induction of symptoms have been identified in satellite RNAs of CMV (24)(25)(26)(27). It has been proposed that these domains are defined by the presence or absence of particular types of secondary structure in the RNA molecule (24,26), although other reports indicate that the primary nucleotide sequence might also be important (27).…”
Section: Discussionmentioning
confidence: 99%